Resistant sources of finger millet genotypes against Pyricularia grisea Sacc. - Naik, R Ganesha; Jayalakshmi, K (Indian Journal of Plant Protection, 2021)
An experiment was undertaken to evaluate seventeen advanced finger millet genotypes (early and medium duration) including two check varieties viz., Indaf 5 (susceptible) and GPU-28 (resistant) against neck and finger blast at Agricultural and Horticultural Research Station, Bavikere, Chickmagaluru district, Karnataka during kharif 2014 to 2016. Genotypes viz., AVT E&M-4, AVT E&M- AVT E&M-7, AVT E&M-9, AVT E&M-10, AVT E&M-13 and AVT E&M-14 showed immune reaction against neck, and finger blast in all the three years of the experimentation. The percent disease incidence (PDI) of neck blast ranged from 0.00 to 19.68 among the genotypes compared to 26.24 PDI in check variety Indaf-5 which showed highly susceptible reaction. In case of finger blast, disease severity ranged from 0.00 to 24.18 per cent, and it was 33.10 PDI in susceptible check Indaf-5 showed highly susceptible reaction. The resistant check variety GPU-28 exhibited resistant reaction to both neck and finger blast. With respect to yield performance, the genotype AVT E&M-14 recorded significantly higher grain yield of 43.90 q/ha and was on par with AVT E&M-13 (41.32 q/ha) and AVT E&M-9 (41.11 q/ha) and AVT E&M -7 (40.44 q/ha) respectively.